Dynamic Interaction of TTDA with TFIIH Is Stabilized by Nucleotide Excision Repair in Living Cells - Giglia-Mari, Giuseppina (Public Library of Science, 2006)
Transcription/repair factor IIH (TFIIH) is essential for RNA polymerase II transcription and nucleotide excision repair (NER). This multi-subunit complex consists of ten polypeptides, including the recently identified small 8-kDa trichothiodystrophy group A (TTDA)/ hTFB5 protein. Patients belonging to the rare neurodevelopmental repair syndrome TTD-A carry inactivating mutations in the TTDA/hTFB5 gene. One of these mutations completely inactivates the protein, whereas other TFIIH genes only tolerate point mutations that do not compromise the essential role in transcription. Nevertheless, the severe NER-deficiency in TTD-A suggests that the TTDA protein is critical for repair. Using a fluorescently tagged and biologically active version of TTDA, we have investigated the involvement of TTDA in repair and transcription in living cells. Under non-challenging conditions, TTDA is present in two distinct kinetic pools: one bound to TFIIH, and a free fraction that shuttles between the cytoplasm and nucleus. After induction of NER-specific DNA lesions, the equilibrium between these two pools dramatically shifts towards a more stable association of TTDA to TFIIH. Modulating transcriptional activity in cells did not induce a similar shift in this equilibrium. Surprisingly, DNA conformations that only provoke an abortive-type of NER reaction do not result into a more stable incorporation of TTDA into TFIIH. These findings identify TTDA as the first TFIIH subunit with a primarily NER-dedicated role in vivo and indicate that its interaction with TFIIH reflects productive NER.